CALCULATION OF PENSION FUND FOR CIVIL SERVANTS IN A PUBLIC UNIVERSITY IN INDONESIA USING THE ACCRUED BENEFIT COST METHOD - Novia SP, Sendari
The pension program is one of the benefits for Civil Servants (PNS). Funds for pension purposes are borne by the State Budget because there is an imbalance between PNS contributions and the pension benefits that will be received. The current civil servant pension fund calculation is based on the last salary of the civil servant. For this reason, civil servant pension funds will be calculated using the Accrued Benefit Cost method based on the average salary of the last 10 years (Final Average Salary) for a number of civil servants in education personnel at a state university in Indonesia. To improve the accuracy of calculations, prediction of the final class of each civil servant is carried out first. The calculation of pension benefits using the Accrued Benefit Cost method involves salary increases between groups, periodic salary increases, and salary increases based on government regulations. With a percentage of salary increases based on the government obtained from predictions that see the trendline regression model. Furthermore, the prediction of the need for pension funds is carried out for the next 20 years. The need for pension funds in the future comes from civil servants who are already on duty and civil servants who are predicted to join the college. For this reason, data will be generated for new civil servants who will serve in a state university in Indonesia. In order for the calculation results to be more accurate, new civil servants who died and new civil servants who resigned will be taken into account within the next 20 years. The generation of new PNS data is carried out using the Poisson distribution whose parameters are obtained by analyzing PNS data for the past 30 years. Taking into account the predictions of the final class of civil servants, prediction of the percentage of salary increases, and predictions of new civil servants in charge can be obtained more accurately the amount of pension fund needs for the next 20 years. The calculation of pension funds using the Accrued Benefit Cost method which is based on the average salary of the last 10 years gives more stable results when compared to the calculation of pension funds using the Accrued Benefit Cost method based on the latest salary.